2019
DOI: 10.3390/genes10100745
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Articular Cartilage and Subchondral Bone of Neonatal and Adult Horses

Abstract: Skeletogenesis is complex and incompletely understood. Derangement of this process likely underlies developmental skeletal pathologies. Examination of tissue-specific gene expression may help elucidate novel skeletal developmental pathways that could contribute to disease risk. Our aim was to identify and functionally annotate differentially expressed genes in equine neonatal and adult articular cartilage (AC) and subchondral bone (SCB). RNA was sequenced from healthy AC and SCB from the fetlock, hock, and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Of these, 27 are unannotated, 43 have published roles in bone formation or fracture and 42 have no known role in bone formation of fracture. However, of these 42 genes, all but five of them have been reported to be expressed in equine bone tissue in publicly available datasets (Kuemmerle et al, 2016, Kemper et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 27 are unannotated, 43 have published roles in bone formation or fracture and 42 have no known role in bone formation of fracture. However, of these 42 genes, all but five of them have been reported to be expressed in equine bone tissue in publicly available datasets (Kuemmerle et al, 2016, Kemper et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 27 are unannotated, 43 have published roles in bone formation or fracture and 42 have no known role in bone formation of fracture. However, of these 42 genes, all but five of them have been reported to be expressed in equine bone tissue in publicly available datasets (Kuemmerle et al, 2016, Kemper et al, 2019). Furthermore, STRING analyses demonstrated that 18 of the 42 genes with no known role in bone encode proteins which interact (directly or indirectly) with proteins that have known roles in bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some tissues can have very heterogenous cellular composition and therefore gene expression pattern. For example, different brain region (Khaitovich et al, 2004) or different muscle fibres types (Rubenstein et al, 2020) can display different gene expression profile. This is especially the case in the heart where previous studies in other species have demonstrated differing ion channel expression not only between atria and ventricles but also within different regions of each chamber such as between the epicardium and myocardium (Bartos et al, 2015;Saadeh, Chadda, et al, 2020;Schram et al, 2002;).…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to subchondral fractures, cysts, cartilage flaps and synovitis (Olstad et al 2011). Much research has studied possible causative factors including genetics, and diet, the relative contribution of which appears to vary (Coskun et al 2016;Kemper et al 2019). Osteoporosis and osteoarthritis in humans, resemble OCDs in horses with loss of articular cartilage and degeneration.…”
Section: Horse Wastagementioning
confidence: 99%